Survey of cases of gonorrhoea caused by penicillinase producing Neisseria gonorrhoeae in the United Kingdom. - Adler, M W (1985)
A postal survey of clinicians working in departments of genitourinary medicine in the United Kingdom was carried out to assess the accuracy of the routine surveillance system for penicillinase producing Neisseria gonorrhoeae (PPNG). A discrepancy was found between the number of cases that had been seen by clinicians and those notified to the Communicable Disease Surveillance Centre. The difference varied from 4% in 1979 to 23% in 1981. This increasing discrepancy presents problems for the control of PPNG strains, as the time when alternative strategies for the treatment of gonorrhoea should be implemented may go unnoticed.